Persistence and mobility of metazachlor and its metabolites in soils: Why transformation products pose a greater groundwater risk - Radka Kodešová; Daniela Tomešová; Martin Kočárek; Miroslav Fér; Aleš Klement; Antonín Nikodem; Jindřich Zelinka; Vít Kodeš (Environmental Geochemistry and Health, 2026)
Abstract Metazachlor is a widely used herbicide that is transformed into various metabolites that are often found in groundwater. To assess their mobility and persistence in the soil environment, batch experiments were performed for the parent compound and two most frequently occurring metabolites OA (479M04) and ESA (479M08), using representative soils of the Czech Republic. In addition, the concentrations of all three compounds and two additional metabolites (479M09 and 479M11) were measured during metazachlor degradation experiments to determine the formation and dissipation rates of all four metabolites. Metazachlor sorbed more strongly and was less persistent than OA and ESA. The sorption of all compounds was positively influenced by the soil organic carbon content, as well as by the sand and silt content, and hydrolytic acidity (metabolites). Dissipation was positively affected by soil organic carbon and clay content and in some cases negatively by sorption. Metazachlor, and particularly OA and ESA, exhibited lower sorption and higher stability in soil than the published values indicate. Even higher stability of four metabolites was observed during the metazachlor transformation. The dissipation of 479M09 (half-live 15–111 days) and 479M11 (39–87) was faster than that of OA (18–492) and ESA (110–231) but much slower than metazachlor dissipation (7–17). The combined formation fractions of four metabolites derived from metazachlor ranged from 60 to 95%. Notably, the yields of OA (27–47%) and potentially carcinogenic 479M09 (10–25%) were significantly higher than database values, suggesting a greater environmental risk than expected.